Ammonium catalyzed cyclitive additions: evidence for a cation–π interaction with alkynes. Issue 11 (5th January 2016) - Nagy, Edith; St.Germain, Elijah; Cosme, Patrick; Maity, Pradip; Terentis, Andrew C.; Lepore, Salvatore D.
Abstract : Ammonium salts accelerate cyclitive additions to carbon–carbon triple bonds via a cation–π interaction as observed by Raman spectroscopy. Abstract : The addition of carbamate nitrogen to a non-conjugated carbon–carbon triple bond is catalyzed by an ammonium salt leading to a cyclic product. Studies in homogeneous systems suggest that the ammonium agent facilitates nitrogen–carbon bond formation through a cation–π interaction with the alkyne unit that, for the first time, is directly observed by Raman spectroscopy.